The Management of Gut Enteric Perforation, Including Clinical Symptoms, in Both Adults and Children a Single Center Study - Musarrat Hussain, Jamshed Alam, Muhib Ullah, Muhammad Jawad Zahid, Uzma Wahid, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: This comparative study evaluated enteric gut perforation's clinical symptoms and management in adults and children. Methods: This single-center study was conducted in the department of surgery, hmc Peshawar, a tertiary care hospital, for two years, between September 2019 to October 2021. The analysis of the medical records of adults and children diagnosed with intestinal perforation who were hospitalized in. Age, gender, length of illness, hemodynamic condition, and first admission testing data were examined. Patients who required extended resuscitation and were operated on more than 24 hours after admission were reviewed for the necessity for a tube laparostomy, operational findings, the kind of surgical therapy administered, and the postoperative outcome. The information was analyzed using SPSS version 23. Results: A total of 194 patients were treated throughout the study period, with 122(62.88%) male and 72(37.12%) female, ranging in age from 3 to 60 (mean 33.5, ± 2.88 years). And the average number of days with symptoms was 5–30 (mean 14.94, ± 8.59 days). All patients (100%) had a high-degree fever and abdominal pain. On abdominal X-rays, pneumoperitoneum was discovered in 145(74.74%) patients. Before surgery, 49(25.25%) patients needed blood transfusions due to anemia. Although 49(25.25%) patients required further resuscitation and tube laparotomies, the first surgical procedures were conducted 24 hours later. 145(74.74%) patients were optimized and operated on within that time. One hundred eight patients (74.48%) had a single perforation, 31 patients (21.37%) had multiple perforations, and six patients (4.13%) had sealed perforations. Primary perforation repair was done in 61(42.06%) patients, while ileostomy was performed in 84 (57.93%) patients. After surgery, intra-abdominal collections were seen in 13 patients (26.53%), a ruptured abdomen in 3 patients (6.12%), and 33 cases (67.34%) of wound infection. Mortality was 7.21% overall. Conclusions: Due to prolonged illness, enteric perforation in adults and children usually presents as hemodynamic instability and sepsis. Thus, surgery is linked to significant morbidity and death rates regardless of the surgical approach. Keywords: Enteric perforation, gut perforation, clinical symptoms, Ileostomy, Tube laparostomy.